Exploring the practice and attitudes of psychiatrists and psychologists towards patient-targeted googling in China - Feng, Yunzi; Hu, Xinyue; Qiao, Yi; Shao, Yang (Frontiers in Psychiatry, 2024)
Background Patient-targeted Googling (PTG) is an unavoidable aspect of the internet era, offering both opportunities and risks. However, no PTG studies have been conducted in Asian contexts to date. Additionally, existing research has provided limited exploration of factors influencing PTG practices, particularly regarding the professional differences between psychiatrists and psychologists. This study seeks to address these research gaps. Method A total of 943 licensed psychiatrists and psychologists working in China completed an online survey. The survey included their attitudes towards PTG (including general attitude, application situations, reasons for/against PTG) and their actual practice of PTG. Results 250(26.5%) respondents reported using PTG. Among them, 151(60.4%) respondents sought consent from clients before use, and 142(56.8%) respondents discussed search results with clients after use. Chinese psychiatrists and psychologists have contradictory attitudes, with concerns but also recognition of its possible positive effects, and expressing a need for more guidance. Compared to psychiatrists or those working in public institutions, psychologists and those working in private institutions report greater concerns about PTG but engage in it more frequently. Conclusions Although the sample is limited, the study reveals notable differences in attitudes and practice of PTG among Chinese psychiatrists and psychologists, which may be related to their distinct professional roles and workplace environments. These findings suggest the need for further research to better understand the underlying factors contributing to these differences. Moreover, the results highlight the importance of developing tailored ethical guidelines and targeted training programs to address PTG practices for psychiatrists and psychologists in China.